Does the John Bates Clark Medal boost subsequent productivity and citation success? - Ho Fai Chan; Bruno S. Frey; Jana Gallus; Benno Torgler (University of Zurich, Department of Economics, 2013)
Despite the social importance of awards, they have been largely disregarded by academic research in economics. This paper investigates whether a specific, yet important, award in economics, the John Bates Clark Medal, raises recipients' subsequent research activity and status compared to a synthetic control group of nonrecipient scholars with similar previous research performance. We find evidence of positive incentive and status effects that raise both productivity and citation levels.
Keywords: A13; C23; M52; 330; awards; incentives; research; John Bates Clark Medal; synthetic control method; Wirtschaftswissenschaft; Preisverleihung; Sozialer Status; Wissenschaftliches Arbeiten; Ökonomen; Vergleich